SMEs in the Philippine manufacturing industry and globalization meeting the development challenges - Aldaba, Rafaelita M. (The Philippine Review of Economics, 2009)
In view of rapid changes in the international trade and the growing complexity of the global production trade and the global production system, this paper reviews the government's small and medium enterprises (SME) policies in the manufacturing sector. It shows that despite the number of policies and programs to improve firm competitiveness, the performance of SMEs has not been vigorously enough to boost the manufacturing industry. [This paper also] highlights the importance of creating a separate government office that would coordinate SME policies and programs to support the integration of SMEs in the global production chain.